PENGEMBANGAN DESAIN DIDAKTIS PRA-ALJABAR UNTUK MEMBANGUN LEARNING TRAJECTORY OF ALGEBRA PADA SISWA SMP KELAS VII - Lia Ardiansari , Annisa Nur Ramadhani (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2018)
The purpose of this research is to formulate or devise a design concept form didaktis algebra and its elements as well as perform operations on algebraic forms based on the learning obstacles that have plagued previous learning students. The design used as learning trajectory of thinking arithmetic to algebraic thinking, researchers call it with pre-algebra. Learning obstacles which will be tested in this study i.e. ontogenic obstacle, didactical obstacle and epistemological obstacle. From the results of the analysis, the researchers offer an expected learning design can minimize barriers to learning (learning obstacles). Design didaktis offered based on the results of such research are compiled based on didactical design research with stages starting from the granting of initial concept in arithmetic, trajectory (liaison), namely the stage of pre-algebra, then the concept of the end (final concept) algebraic formally.